The Decline of Ideology and Rise of Political Pragmatism Among Kiai in Post-Authoritarian Indonesia - Maram, Ahmad Nabilul; Busyairi, Ahmad; Assidiqi, Muhammad Raqib (Yayasan Pesantren Mahasiswa An-Nur, 2023)
This article discusses the significant role of pesantren in Indonesian politics. Pesantren institutions substantially influence shaping political perspectives, recruiting leaders, and organizing communities. During the New Order era, some pesantren supported the government to maintain political stability, while others were involved in Islamic political movements opposing the regime. Following the political reform in 1998, pesantren became more actively engaged in practical politics by supporting specific candidates or political parties and promoting Islamic values in political discourse. The research employs a qualitative method, analyzing relevant documents and literature and discussing the history of pesantren in Indonesian politics. It highlights the phenomenon of political pragmatism among kiai (Islamic scholars) and its impact on political dynamics. Pesantren and Kiai are central in shaping political perspectives, mobilizing the masses, and influencing policy-making.